2018
DOI: 10.1016/j.jbusres.2017.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Managing customer relationships in the emerging markets – guanxi as a driver of Chinese customer loyalty

Abstract: Guanxi, a social exchange mechanism built on mutual favors, is an integral part of Chinese culture and a necessary relationship management tool for businesses operating in the People's Republic of China (PRC). This paper uses the cognition-affect-conation trajectory to illustrate the subtle differences between Guanxi approach and the conventional relationship marketing approaches on customer loyalty and word-of-mouth intentions. This process is mediated by calculative trust and affective attitude toward the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 112 publications
(138 reference statements)
4
62
0
2
Order By: Relevance
“…It is well noticing that RC can enhance the profitability of Chinese textile companies. This is because that good relationships with customers in China where guanxi plays an important role in Chinese culture can enable companies to build company's reputation and gain customers' loyalty [77,78]. However, in Korea, the analysis shows that corporate profitability is positively correlated with only CEE, HCE, and SCE.…”
Section: Discussionmentioning
confidence: 97%
“…It is well noticing that RC can enhance the profitability of Chinese textile companies. This is because that good relationships with customers in China where guanxi plays an important role in Chinese culture can enable companies to build company's reputation and gain customers' loyalty [77,78]. However, in Korea, the analysis shows that corporate profitability is positively correlated with only CEE, HCE, and SCE.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, a most recent study finds that guanxi including the attribute CF is significantly related to WoM intentions among Chinese bank customers (Lee et al, 2018). In short, studies have consistently shown that the spread of favourable WoM communication benefits from the establishment of strong customer ties (Balaji et al, 2016;Brown and Reingen, 1987;Wirtz and Chew, 2002).…”
Section: Hpa1mentioning
confidence: 97%
“…Furthermore, turbulent times and institutional voids which are common in emerging markets call for effective relationship management with different stakeholders in order to remain legitimate and robust in those countries (Lee et al, 2018;Salmi and Heikkila, 2015;Ghauri et al, 2014).…”
Section: Robustnessmentioning
confidence: 99%